Organic vs. conventional: impact of cultivation treatments on the soil microbiota in the vineyard - Colautti, Andrea; Civilini, Marcello; Contin, Marco; Celotti, Emilio; Iacumin, Lucilla (Frontiers in Microbiology, 2023)
The aim of this study was to compare the effects of two vineyard management practises on the soil 17 and its associated microbiota. The experiments were conducted in two adjacent plots, one completely 18 organically managed and the other conventionally managed in terms of phytosanitary treatments but 19 fertilized with organic amendments. The chemical soil analyses were correlated to the prokaryotic 20 and fungal communities, which were studied using the metabarcoding technique. The main 21 difference between the two treatments was a significantly higher amount of Cu in the organic 22 managed vineyard soil, while conventional managed soil presented higher concentration of Na and 23 Mg and was also associated with higher pH values. Despite these differences, no significant 24 diversities were observed on soil biodiversity and microbial composition considering alfa and beta 25 diversity metrics. However, the percentages of some phyla analysed individuallydiffered significantly 26 between the two managements. Analysing the metabolisms of these phyla, it was discovered an 27 increment of species correlated to soils with higher organic matter content or land not used for 28 agricultural purposes in the organic treated soil. The findings indicate that, despite the use of copper-29 based phytosanitary products, there was no degradation and loss of biodiversity in the organic soil 30 microbial population compared to conventional management with the same type of fertilisation, and 31 the observed microbial population was more similar to that of natural soils.